PERENCANAAN DAN PEMBUATAN MESIN POTONG KAYU - H. Midi H. Midi; Rudi Siswanto Siswanto (Scientific Journal of Mechanical Engineering Kinematika, 2016)
Main purpose of this final task is to design a wood cutter machine for channel saw on the wood board and to get the final result like a work sheet and to determine the machine component of the wood cutter until it’s proper to built. This design of the modification wood cutter machine has some concept with some steps like: need, problem analysis and product specification, product concept design, analysis technique, modeling and the work sheet. the next process is build the wood cutter machine that has been planned. The final task result is a design that poured in the work sheet include the framework machine drawing, liner drawing, arm connector drawing, arm knife drawing, pen drawing, pivot transmission drawing, pivot eccentric drawing, circle eccentric drawing, puli and workspace drawing. The wood cutter capacity saw could reach 2 cm thickness. The machine booster resources is an electricity engine with 0.25 HP power. The wood cutter from modification product dimension length x wide x height that 350 x 350 x 910 mm. the machine framework material use an iron steel profile L 30 x 30 x 2 mm material St 42. The transmission pivot made from St 37 with dimension O 15 mm and 300 mm length. The transmission system use belt component V and two pair of Puli 1,5’’ and 3.5’’, work base board use Plywood. The final result of this design and the wood cutter making then will be built adjust the work sheet.